DNA sequencing, genomes and genetic markers of microbes on fruits and vegetables. Issue 2 (24th March 2020) - Shen, Youming; Nie, Jiyun; Kuang, Lixue; Zhang, Jianyi; Li, Haifei
Summary: The development of DNA sequencing technology has provided an effective method for studying foodborne and phytopathogenic microorganisms on fruits and vegetables (F & V). DNA sequencing has successfully proceeded through three generations, including the tens of operating platforms. These advances have significantly promoted microbial whole‐genome sequencing (WGS) and DNA polymorphism research. Based on genomic and regional polymorphisms, genetic markers have been widely obtained. These molecular markers are used as targets for PCR or chip analyses to detect microbes at the genetic level. Furthermore, metagenomic analyses conducted by sequencing the hypervariable regions of ribosomal DNA (rDNA) have revealed comprehensive microbial communities in various studies on F & V. This review highlights the basic principles of three generations of DNA sequencing, and summarizes the WGS studies of and available DNA markers for major bacterial foodborne pathogens and phytopathogenic fungi found on F & V. In addition, rDNA sequencing‐based bacterial and fungal metagenomics are summarized under three topics. These findings deepen the understanding of DNA sequencing and its application in studies of foodborne and phytopathogenic microbes and shed light on strategies for the monitoring of F & V microbes and quality control. Abstract : The principles of three generations DNA sequencing were depicted. Whole genome sequencing and DNA markers of foodborne and plant fungal pathogens were summarized. Bacterial and fungal metagenomics studies on fruits and vegetables were concluded.